PENDIDIKAN BIOLOGI SEBAGAI UPAYA PREVENTIF TERHADAP KEKERASAN ANAK : STUDI PADA GURU SEKOLAH MENENGAH PERTAMA - Rizkiyah, Fitri; Haerani, Yeni (Jurnal Ilmiah Pendidikan dan Keislaman, 2025)
Violence against children is a crucial issue that has a broad impact on children’s psychological and physical development. Teachers, as central figures in the primary education environment, have a strategic role in preventing this violence. This study aims to examine the potential integration of biology education as a preventive measure against child violence. This study uses a qualitative approach with a case study research type. The data collection technique was interviews with three science teachers who teach at the junior high school level. The interview guide used included indicators of biology learning integrated with violence prevention efforts based on the possible impacts. The results of the study on junior high school teachers indicate that biology education has great potential as a preventive medium against child violence if integrated contextually with character education. Training and curriculum support are essential so that biology materials do not only focus on cognitive aspects, but also on affective aspects.